استراتيجيات تعلم اللغة العربية لدى طلبة كلية الدراسات الإسلامية بجامعة الأمير سونكلا نكرين شطر فطاني (PSU) - فاندينج، تانونج ساك (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
This study aims to investigate strategies used in learning Arabic language employed by students at Faculty of Islamic Studies of Prince of Songkla University, Pattani. It also aims to study effects of certain independent variables in the use of language learning strategies: gender and level of interest in Arabic language. This study adopted a quantitative method to collect data. The populations were 180 first-year students from various majors of Faculty of Islamic Studies. Strategy Inventory for Language Learning (SILL) developed by Oxford (1990) was used as an instrument for the study. The results show that the students of Faculty of Islamic Studies adopted six language learning strategies at the medium level. Among these six strategies, the most frequently used was metacognitive strategy, followed by affective, compensation, memory and social strategies respectively, whereas the least frequently used was cognitive strategy. Findings also show that gender influences the use of strategies in which female students used learning strategies more often than male students, and both female and male students were in the middle level of use but did not show significant difference in the use except for the use of metacognitive strategy. The results also highlight that the use of language learning strategies according to level of interest in Arabic language was in the medium level. There was no significant difference in the use at all levels of interest in Arabic except for the use of memory and cognitive strategies which only indicate the significant difference. Furthermore, the results also demonstrate that the higher the level of interest in Arabic language, the higher the tendency of students to use the six language learning strategies. From these findings, the use of strategies to learn Arabic as a second language or a foreign language has become an urgent and necessary need.